A rare maternal gastrointestinal stromal tumor found in the second trimester of pregnancy: A case report - Naoko Tanaka; Shoko Tamada; Naoko Ueno; Makoto Ishida; Junichi Kodama; Tetsushi Kubota (Elsevier, 2020)
Gastrointestinal stromal tumors are rare, and in pregnancy they are extremely rare. We present a case of a maternal gastrointestinal stromal tumor found in the second trimester of pregnancy. A 29-year-old woman, gravida 1 para 0, complained of bloody vomiting at 14 weeks of gestation. She had no significant medical history. We performed plain computed tomography and upper gastrointestinal endoscopy. Precise examination revealed a large mass in the stomach and an exposed blood vessel on the surface. An exposed blood vessel can be harmful for mother and fetus as it might rupture during the pregnancy. We performed a distal gastrectomy at 16 weeks of gestation. Histology confirmed a localized gastrointestinal stromal tumor with a high risk of recurrence, and adjuvant imatinib was recommended. The patient elected to delay adjuvant imatinib until after delivery. The postoperative and antenatal course was favorable, and the patient was followed up by ultrasound every 2 months after the operation. After she gave birth at 40 weeks of gestation, she started adjuvant imatinib 400 mg/day. There was no evidence of recurrence 1 year after surgery. There are no guidelines for the management of gastrointestinal stromal tumors in pregnancy. Given the treatment challenges, we believe that pregnant patients should be managed by a multidisciplinary team with expertise in gastrointestinal tumors and fetal-maternal medicine.